2019
DOI: 10.3390/rs11080975
|View full text |Cite
|
Sign up to set email alerts
|

SPICE-Based SAR Tomography over Forest Areas Using a Small Number of P-Band Airborne F-SAR Images Characterized by Non-Uniformly Distributed Baselines

Abstract: Synthetic aperture radar tomography (TomoSAR) has been proven to be a useful way to reconstruct vertical structure over forest areas with P-band images, on account of its three-dimensional imaging ability. In the case of a small number of non-uniformly distributed acquisitions, compressive sensing (CS) is generally adopted in TomoSAR. However, the performance of CS depends on the selected hyperparameter, which is closely related to the noise of a pixel. In this paper, to overcome this limitation, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…This greatly limited the possibility of not detecting the actual tree because individual tree canopies were not often connecting, as is mentioned by [27]. The limitations of the IWS segmentation from ULS data in close canopy forest were tested and compared with several other methods by [15]. The study of [26] mentioned reaching high detection potential of individual standing trees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This greatly limited the possibility of not detecting the actual tree because individual tree canopies were not often connecting, as is mentioned by [27]. The limitations of the IWS segmentation from ULS data in close canopy forest were tested and compared with several other methods by [15]. The study of [26] mentioned reaching high detection potential of individual standing trees.…”
Section: Discussionmentioning
confidence: 99%
“…In both highly-cited studies [10,11], the TLS method was used for data acquisition, and both author collectives concluded that the method was time-demanding. In contrast to TLS, the ULS data acquisition provides lower point cloud density matched with high time efficiency [12][13][14][15]. A yearlong investigation of the branch inclination angles using TLS was not performed on forest trees.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of canopy cover on tree detection accuracy has not been evaluated. In a recent study [53], different tree-crown detection algorithms were assessed under various canopy cover conditions and a reduction in accuracy directly related to an increase in canopy cover rate was reported. However, the authors report a high dependency on spatial resolution of the tree detection methods and did not employ deep learning techniques.…”
Section: Input Data Products Performance Vs Image Resolutionmentioning
confidence: 99%